Język polityki w nazwach ulic? Przypadek Warszawy = Political language in street names? The case of Warsaw - Kłos, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Streets had names as early as ancient Rome. These city roads "spoke" and conveyed significant meaning. Such was the via Sacra - ?sacred road?. From the Middle Ages to the 18th century, streets bore topographic names derived from the professions of the townspeople or from the names of saints. The first ?symbolic? names appeared in Warsaw at the beginning of the 19th century. These were "commemorative" names with quasi-political content (e.g. Napoleon Street).
Keywords: język polityki; nazwy ulic; Warszawa; language of politics; street names; Warsaw